Spiritual Distress in Bereavement: Evolution of a Research Program - Burke, Laurie A. (Religions, 2014)
Many mourners turn to their spiritual beliefs and traditions when confronted by the death of a loved one. However, prior studies have either focused primarily on the benefits of faith following loss or studied spiritual struggle outside the context of bereavement. Moreover, scales to measure bereavement-related crises of faith and interventions specifically designed for spiritually inclined, distressed grievers are virtually non-existent. Our program of research, which to date has consisted of working with Christian grievers and is outlined below, elucidates complicated spiritual grief (CSG)—a spiritual crisis following the loss of a loved one. For example, our longitudinal examination of 46 African American homicide survivors established the relation between positive religious coping, CSG, and complicated grief (CG), to clarify whether religious coping more strongly predicted bereavement distress or vice versa, with a follow-up study that determined the relation between religious coping and posttraumatic stress disorder (PTSD) and depression. We replicated and expanded these findings with a diverse sample of 150 grievers to explore the complex relation between CSG, CG, and meaning making in a comparison study of mourners who had experienced traumatic-versus natural death losses. In a companion study, we qualitatively analyzed 84 grievers’ narratives and interviewed a 5-member focus group to capture and learn from their firsthand experiences of spiritual distress. To close the gap in terms of CSG assessment, we also developed and validated the Inventory of Complicated Spiritual Grief (ICSG). Currently, our ongoing CSG investigation extends in several directions: first, to a sample of family members anticipating the loss of their hospice-eligible loved one in palliative care; and, second, to the development and testing of a writing-intensive intervention for newly bereaved, spiritually inclined grievers.